EFFICIENCY OF THE PROLONGED THERAPY BY THE ANTISECRETORY MEDICATIONS IN THE REDUCTION OF THE POSTHELICOBACTERIAL GASTRITIS RISKS AMONG THE CHILDREN - E.A. Potrakhova; N.V. Sobotyuk; A.V. Kononov (Union of pediatricians of Russia, 2008)
The authors studied the efficiency of the 3 months long therapy by Rabeprazole after eradication of the causative agent in the children with h. pylori associated gastritis from the high risk group of the development post helicobacter gastritis. They demonstrated that most children with h. pylori associated gastritis, who have un favourable prognostic factors, have persistence of the inflammatory infiltrate in the mucosa of the antral stomach after eradication, which is accompanied with the elevated secretion of the hydrochloric acid and development of the acid dependent diseases. The use of the anti secretory medications during 3 months after h. pylori eradication among these children allows one to prevent the development of the gastritis and its complications.Key words: h. pylori_associated gastritis, eradication of h. Pylori, children, rabeprazole.